STRATEGI PEMULIHAN PEREKONOMIAN UMKM SEKTOR KULINER PASCA PANDEMI COVID-19 DI KOTA LUBUK LINGGAU - Metha Aditya Pradesa (Jurnal Interprof, 2022)
The purpose of this writing is to find out the strategy for the recovery of the small and medium-sized culinary economy in the post-covid-19 pandemic in Lubuk Linggau City. The research method used in qualitative descriptive research, data collection techniques using documentation techniques, namely collecting data from various reference sources. The results of the research are that the Covid 19 pandemic has had an extraordinary impact on the performance of MSMEs in Indonesia, this can be seen from the conditions before Covid-19. MSMEs that are able to survive in the midst of the Covid-19 climate include MSMEs that are already connected to the digital ecosystem by utilizing marketplaces in Indonesia.